Visibility of Learning Media of a Culinary-Based Electronic Magazine in Blended Learning - Anggri Sekar Sari; Ika Wahyu Kusuma Wati (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
This study aims to produce media products that use culinary-based electronic magazines on blended learning. The method used in this study was research and development. The procedure of media development used the Four-D model to produce learning media based on blended learning. The stages of the study consisted of define, design, development, and dissemination. The stages of development used alpha testing for product validation by learning experts, material experts, and media experts. After that the stages of dissemination, beta testing was performed by testing the product on users in small groups. The subjects of this study were students in foodservice expertise. The results of this study showed that the alpha tests on aspects of media and materials and learning both obtained very high criteria. Furthermore, the average score of all aspects was more than 89% with reasonable criteria. while the beta test results indicated high criteria with the average of students’ reached 86%, categorized as feasible.